Digitalization Strategy for Consignment, Franchising, and Partnership Networks Through the Implementation of e-KOlab (Electronics for Consignments, Franchising, Organizational Networks) (Study on MSMEs member of DPD IWAPI Bali Association) - Farida, Farida; Febrianty, Febrianty; Budilaksono, Sularso; Suryani, Ni; Gorda , A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The province of Bali as a tourism area is feeling the impact of the Covid 19 pandemic. The indicator is the decline in the number of MSMEs. IWAPI (Indonesian Women Entrepreneurs Association) Bali Province which fosters MSMEs and Cooperatives as partners in this research requires a strategy that moves many elements to collaborate and co-optise together. The purpose of this study is: to bring together institutions, capital and MSME actors through digitalization or applications. The purpose of developing the application is to encourage MSMEs owned by Balinese women to operate locally with global quality. The research method used in this study is the OODA (Observe, Orient, Decide and Act) method. The first step is observation by collecting and observing primary data and secondary data of SMEs/IWAPI assisted. The second step is orientation by conducting root causal analysis with fishbone, SWOT and analysis of service policies towards MSMEs/IWAPI assisted, especially during pandemic recovery. The third step is Decide, namely developing e-collaborations. The last step is Act: implementation of e-collaboration, readiness testing there is application of e-collaboration. The e-Kolab application is a strategy for SMEs Scale Up and can be a Model Business Continuity Plan (BCP) in conducting business collaborations to apply the principle of local wisdom "PangPadePayu". The short-term strategy of this application will provide a digital service boost for MSME actors. While the long-term strategy is to build digital technology as a platform in MSME business processes; and the development of modern MSME business models.